A triple deletion of the secreted aspartyl proteinase genes SAP4, SAP5, and SAP6 of Candida albicans causes attenuated virulence. - Sanglard, D (1997)
Secreted aspartyl proteinases (Saps) from Candida albicans are encoded by a multigene family with at least nine members (SAP1 to SAP9) and are considered putative virulence factors important for the pathogenicity of this human pathogen. The role of Sap isoenzymes in the virulence of C. albicans has not yet been clearly established, and therefore, using recent progress in the genetics of this yeast, we have constructed a panel of isogenic yeasts, each with a disruption of one or several SAP genes. We focused on the construction of a C. albicans strain in which three related SAP genes (SAP4, SAP5, and SAP6) were disrupted. Growth of the delta sap4,5,6 triple homozygous null mutant DSY459 in complex medium was not affected, whereas, interestingly, growth in a medium containing protein as the sole nitrogen source was severely impaired compared to the growth of the wild-type parent strain SC5314. Since the presence of Sap2 is required for optimal growth on such medium, this suggests that Sap4, Sap5, or Sap6 plays an important role for the process of induction of SAP2. When guinea pigs and mice were injected intravenously with DSY459, their survival time was significantly longer than that of control animals infected with the wild-type SC5314. Attenuated virulence of DSY459 was followed by a significant reduction of yeast cells in infected organs. These data suggest that the group of Sap4, Sap5, and Sap6 isoenzymes is important for the normal progression of systemic infection by C. albicans in animals.